An Educational Pilgrimage to the United States. Un pèlerinage psycho-pédagogique aux États-Unis. : Travel Diary of Raymond Buyse, 1922. Carnet de voyage de Raymond Buyse, 1922. - Buyse, Raymond, 1889-1974 (Book collections on Project MUSE., 2011)
In 1922, Raymond Buyse, a young Belgian 'pedologist', undertook, together with the famous Dr. Ovide Decroly, a study tour of the United States of America. Both were interested in the 'scientific' study of the child and especially in applied American psychology. They met well-known American professors and visited universities that were developing these aspects of educational psychology. Back in Belgium, they dedicated several books and articles to the issues discussed during the trip. Less known is that Raymond Buyse noted his impressions and reflections of the trip in a diary. Buyse writes in a lively style about his encounters with the 'great' psychologists and pedagogues of that time and in doing so this diary adds a new dimension to the study of the history of educational psychology in Belgium and far beyond.